2022
DOI: 10.1002/ase.2162
|View full text |Cite
|
Sign up to set email alerts
|

One year of anatomy teaching and learning in the outbreak: Has the Covid‐19 pandemic marked the end of a century‐old practice? A systematic review

Abstract: At the end of 2019, the Covid-19 pandemic spread caused restrictions in business and social spheres. Higher education was also severely affected: universities and medical schools moved online to distance learning and laboratory facilities closed. Questions arise about the long-term effects of this pandemic on anatomical education. In this systematic review, the authors investigated whether or not anatomical educators were able to deliver anatomical knowledge during this pandemic. They also discuss the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 125 publications
(142 reference statements)
3
68
0
Order By: Relevance
“…These accounts document emergency remote teaching (Hodges et al, 2020) rather than pre-planned implementation, and few studies have been able to examine the early outcomes (Thom et. al, 2021;Yoo et al, 2021;Papa et al, 2022). There are few descriptions in the literature of planned, fully online anatomy courses.…”
Section: Online Anatomy Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…These accounts document emergency remote teaching (Hodges et al, 2020) rather than pre-planned implementation, and few studies have been able to examine the early outcomes (Thom et. al, 2021;Yoo et al, 2021;Papa et al, 2022). There are few descriptions in the literature of planned, fully online anatomy courses.…”
Section: Online Anatomy Educationmentioning
confidence: 99%
“…Gross anatomy is a pillar of human health sciences education (Rizzolo, 2002; Drake et al, 2009; Sugand et al, 2010; Standring, 2016; Ross et al, 2021); therefore, it is essential that its offering in an online distance format be implemented carefully and strategically using evidence‐based practices. In 2020, gross anatomy educators began to publish reports about the development of online courses in response to the Covid‐19 pandemic (Cuschieri & Calleja Agius, 2020; Naidoo et al, 2020) as well as the impact of Covid‐19 on anatomy teaching (Papa et al, 2022). These accounts document emergency remote teaching (Hodges et al, 2020) rather than pre‐planned implementation, and few studies have been able to examine the early outcomes (Thom et.…”
Section: Introductionmentioning
confidence: 99%
“…In this period, classes were held in a hybrid manner; some classes were online and some stationary, which could also be one of the causes of stress. Students did not have the time and opportunity to establish new relationships and integrate, which usually takes place in the first months of the first year of studies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric studies permit the identification of therapeutic interventions with potential risk for neurovascular tissues that other methods do not permit [ 15 ]. This study found that needling insertion of the supinator muscle at Frohse arcade with both approaches provided enough space to avoid penetration of the neurovascular bundle, particularly if the procedure was US-guided.…”
Section: Discussionmentioning
confidence: 99%